MODEL PENGEMBANGAN PERIKANAN DI PERAIRAN SELATAN JAWA - Tri Wiji Nurani; John Haluan; Sudirman Saad; Ernani Lubis (Buletin PSP, 2007)
Development of fishery activity shall be conducted base on the characteristic of potency owned by a territotial water region. South Java water region has a characteristic condition of fisheries resources which need a specific management. Based on a fishery resources potency, South Java water region has a very big potency, but fishery activity just develop in a certain places only, namely Palabuhan Ratu, Cilacap and Prigi. The research has aim to build a model of fisheries development which is adopted by a regional characteristic. Method of the system approach used to analyse the problem and develop the model. System engineering compiled in a model with three submodels are 1) fishery effort (submodel USAHA), 2) requirement of PP/PPI, functionality and accessability (submodel PELABUHAN) and 3) policy and institution (submodel LEMBAGA). Firstly model determined commodity’s priority, strategy of model implementation using interpretative structural modellig (ISM) technique. The study resulted two models are 1) tuna fisheries development model and 2) coastal fisheries development model. At tuna fisheies development model, its expressed that tuna fishery business represent a high risk business, the government policy which do not support the business like increasing the fuel price giving big impact for continuing the business. Fishing port which capable to support tuna fishery’s business are PPS Cilacap and PPN Pelabuhan Ratu. Developments are require to be done by the intregrated institution which can accommodate the stakeholder needs. At the model of fisheries coastal development, the commodity’s priority are bonito, skipjack, white pomfret, hair tail, lobster, shrimp and anchovy. Fishery business covering gillnet multifilament, gillnet monofilament, purse seiner, trolling,’payang’, trammel net and ‘pancing rawai’. The effort can be done in middle scale or small scale. Existing PP/PPI mostly can be able to support fisheries acivity in each region. Role of KUD, HNSI and group of fisherman require to be improved for fisherman empowerment. Strategy of implementation model require to pay attention to the system which is a key element for succeeded the system.